The Implementation of Spelling Bee Game in Vocabulary Mastery at X Class of MA Miftahul Ulum Bettet Pamekasan - Seregar, Riyan Fitri; YB, Dinar Vincy (DIDAKTIKA, 2024)
The aim of this research is to know the implementation of spelling bee game in mastering students' vocabulary and to know the difficulties faced by students in developing vocabulary. In This research, research design used descriptive qualitative. The way the researcher obtained data was by using observations, interviews, questionnaires and documentation, while the research subject was class X MA Miftahul Ulum Bettet Pamekasan students consisting of 28 students. while the results of this research are the process of implementing the spelling bee game with 4 steps, namely; form a group, practice, apply it, the one who gets the highest points is the winner. from data obtained from field research regarding the difficulties faced by students in developing vocabulary, namely the problem of the difference between pronunciation and writing in English consisting 8 students, the problem of using vocabulary in English consisting 7 students, the problem of differences in writing and spelling consisting of 9 students. and finally the problem of difficulty distinguishing Indonesian letters from English was 4 students.Â